Assessment of Ocriplasmin Effects on the Vitreoretinal Compartment in Porcine and Human Model Systems - Bart Jonckx; Michael Porcu; Aurelie Candi; Isabelle Etienne; Philippe Barbeaux; Jean H. M. Feyen (Journal of Ophthalmology)
Ocriplasmin (Jetrea®) is a recombinant protease used to treat vitreomacular traction. To gain insight into vitreoretinal observations reported after ocriplasmin treatment, we have developed an in vivo porcine ocriplasmin-induced posterior vitreous detachment (PVD) model in which we investigated vitreoretinal tissues by optical coherence tomography, histology, and cytokine profiling. Eight weeks postinjection, ocriplasmin yielded PVD in 82% of eyes. Subretinal fluid (85%) and vitreous hyperreflective spots (45%) were resolved by week 3. Histological analysis of extracellular matrix (ECM) proteins such as laminin, fibronectin, and collagen IV indicated no retinal ocriplasmin-induced ECM distribution changes. Retinal morphology was unaffected in all eyes. Cytokine profiles of ocriplasmin-treated eyes were not different from vehicle. In cell-based electrical resistance assays, blood-retinal barrier permeability was altered by ocriplasmin concentrations of 6 μg/mL and higher, with all effects being nontoxic, cell-type specific, and reversible. Ocriplasmin was actively taken up by RPE and Müller cells, and our data suggest both lysosomal and transcellular clearance routes for ocriplasmin. In conclusion, transient hyperreflective spots and fluid in a porcine ocriplasmin-induced PVD model did not correlate with retinal ECM rearrangement nor inflammation. Reversible in vitro effects on blood-retinal barrier permeability provide grounds for a hypothesis on the mechanisms behind transient subretinal fluid observed in ocriplasmin-treated patients.